Ketergantungan Emosional Terhadap Ibu Pada Mahasiswa - nanik, rosalia (Jurnal Psikoedukasia, 2026)
The absence of a father figure in the lives of college students, or what is known as fatherlessness, can lead to excessive emotional attachment to the mother as the sole caregiver. This study aims to understand the form of emotional dependence on the mother, the factors that influence it, and its impact on the independence and psychological well-being of fatherless college students. This study employs a qualitative approach using phenomenological methods with four participants who experienced fatherlessness due to divorce or the death of their father. Data collection techniques include in-depth interviews, observation, and documentation. The results indicate that forms of emotional dependence include a need for validation, anxiety when separated from the mother, and difficulty making decisions independently. Factors contributing to emotional dependency include protective parenting styles, trauma from losing a father, and lack of social support. The resulting impacts include difficulties in emotional regulation, low self-control, and inability to form healthy relationships outside the family. Participants demonstrated coping strategies such as seeking emotional support from their mothers, engaging in activities, and using spiritual approaches. These findings have important implications for counseling services in higher education, such as the need for emotion-based group counseling and strengthening self-development programs to help students build adaptive emotional independence.